Understanding Disability, Inclusion and Social Activity Participation - Johner, Randy (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
As the recognition of social inclusion intensifies worldwide, it is important to broaden our understanding of various linkages between disability and social deprivation. This paper examines the links between disability and specific social relations/emotional activities which are important to well-being, quality of life and inclusion. Using a stratified randomly-selected sample of Saskatchewan single mothers (n=370), this paper compared social relations/emotional activity participation among single mothers with a disability and single mothers without a disability. Overall, study results indicate that single mothers with a disability, particularly those of Aboriginal ethnicity, were socially deprived. Increased income resources and focussed service-provider interventions are necessary in order to equalize access for social relations/ emotional activity participation needs of this population of single mothers.